One-Pot Palladium-Catalyzed Synthesis of Benzo[b]carbazolediones - Do, Hoang Huy; Tran, Hung Quang; Ohlendorf, Lars; Ngo, Thang Ngoc; Dang, Tuan Thanh; Ehlers, Peter; Villinger, Alexander; Langer, Peter (Synlett, 2015)
A palladium-catalyzed one-pot reaction for the synthesis of benzo[b]carbazolediones is described which proceeds by amination of 2,3-dibromonaphthoquinone, Suzuki cross-coupling with (2-bromophenyl)boronic acid, and subsequent intramolecular C–N Buchwald–Hartwig cyclization with amines.
Keywords: cyclizations; one-pot reaction; Suzuki–Miyaura reaction; Buchwald–Hartwig reaction; palladium